A multi-criteria assessment of policies to achieve the objectives of the EU marine litter strategy. (July 2022) - Dias, Luis C.; Cunha, Maria C.; Watkins, Emma; Triantaphyllidis, George
Abstract: This paper proposes and assesses policy options to achieve the objectives of the EU marine litter strategy, based on the existing EU legislation. A group of experts and stakeholders was involved through a multi-staged workshop organized to generate the information to assess the contribution of the policies to the set of objectives, as well as the relative importance of the objectives, on qualitative scales. The ELECTRE TRI multi-criteria decision analysis method was used to rate the policies, which were subsequently ranked. Per the results, all policies deserve to be considered, even when the more pessimistic assessments (33rd percentile) are used. Revising the Urban Wastewater Treatment Directive, setting legislative targets on marine litter and ensure they are fully monitored, and funding proven clean-up technologies were deemed to be the most potentially impactful policies. The remaining policies assessed can nevertheless play an important role in complementing the higher-ranked policies. Highlights: Policy options aligned with the EU marine litter strategy are proposed and assessed. Multi-criteria approach to rate and rank policy options evaluated qualitatively Experts and stakeholders were involved through a multi-staged workshop. The emerging consensus deems that all the policies proposed would be positive.